Structural determinants of DNA recognition by plant MADS-domain transcription factors. Issue 4 (25th November 2013) - Muiño, Jose M.; Smaczniak, Cezary; Angenent, Gerco C.; Kaufmann, Kerstin; van Dijk, Aalt D.J.
Abstract: Plant MADS-domain transcription factors act as key regulators of many developmental processes. Despite the wealth of information that exists about these factors, the mechanisms by which they recognize their cognate DNA-binding site, called CArG-box (consensus CCW6 GG), and how different MADS-domain proteins achieve DNA-binding specificity, are still largely unknown. We used information from in vivo ChIP-seq experiments, in vitro DNA-binding data and evolutionary conservation to address these important questions. We found that structural characteristics of the DNA play an important role in the DNA binding of plant MADS-domain proteins. The central region of the CArG-box largely resembles a structural motif called 'A-tract', which is characterized by a narrow minor groove and may assist bending of the DNA by MADS-domain proteins. Periodically spaced A-tracts outside the CArG-box suggest additional roles for this structure in the process of DNA binding of these transcription factors. Structural characteristics of the CArG-box not only play an important role in DNA-binding site recognition of MADS-domain proteins, but also partly explain differences in DNA-binding specificity of different members of this transcription factor family and their heteromeric complexes.